Pengembangan Modul Kalkulus dengan Pemanfaatan Software Geogebra - Isnaini Nur Azizah; Muhammad Khoirul Amri; Fertilia Ikashaum; Mispani Mispani (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2021)
This study aims to produce a calculus module using geogebra software on limits, derivatives, and integrals. This research uses the 4D Thiagarajan development. This method is modified into 3D, thats define, design, and development. This research begins with a need’s analysis covering student analysis, material analysis, task analysis, analysis of the formulation of learning objectives. The results of the needs analysis that the calculus module using geogebra applications needs to be developed. Based on the results of the student and teacher questionnaire responses said the module developed was very good with a value of 81%.